Impact of tax revenue on economic growth: A study from Cambodia - Kong Chantha (Ho Chi Minh City Open University Journal of Science - Economics and Business Administration)
The study examines the impact of tax revenue on economic growth in Cambodia from 1994 to 2022. The Autoregressive Distributed Lag (ARDL) method is applied to test the cointegration between variables. It analyzes long- and short-run dynamics between tax revenue and economic growth, considering special taxes, public expenditure, and the service sector’s growth. The findings reveal a significant positive association between tax revenue and economic growth in the long run, indicating that a 1% increase in tax revenue leads to a 0.11% increase in economic growth, while special taxes positively impact economic growth. However, public expenditure exhibits a negative relationship with long-term growth. Moreover, the growth of the service sector emerges as a vital driver of economic expansion. The short-run dynamics suggest fluctuations in tax revenue’s impact on economic growth. The regression model exhibits high explanatory power, with diagnostic tests confirming its reliability. Therefore, The Royal Government should balance and optimize tax laws and regulations, continually amending and compiling them. Additionally, consistent policies and strategic plans should be established to prevent tax evasion and eliminate corruption in tax affairs.